Norman Fairclough, New Labour, New Language?, London: Routledge, 2000, 178 s., 16.99; Anthony Giddens, The Third Way and its Critics, Cambridge: Polity Press, 2000, 189 s., 15.96; Anthony Giddens, Runaway World. How Globalisation is Reshaping Our Lives, - Hermann, Stefan (Politica, 2001)
Norman Fairclough, New Labour, New Language?, London: Routledge, 2000, 178 s., 16.99; Anthony Giddens, The Third Way and its Critics, Cambridge: Polity Press, 2000, 189 s., 15.96; Anthony Giddens, Runaway World. How Globalisation is Reshaping Our Lives, London: Profile Books, 1999, 104 s., 14.36; Anthony Giddens and Will Hutton (eds.), On the Edge. Living with Global Capitalism, London: Jonathan Cape, 2000, 241 s., 19.96.